Maintenance suppression reduces the accessibility of visual information in working memory regardless of its normative valence - Jerinic-Brodeur, Caleb N.; Banich, Marie T.; Lewis-Peacock, Jarrod A. (Frontiers in Cognition, 2024)
Intentional removal of unwanted information allows us to focus on our current goals. Previous research has shown that suppressing the maintenance of neutral images in working memory can impair access to that information in immediate and delayed memory tests. However, it remains unclear whether maintenance suppression has the same impact on emotionally valenced images. Intrusive thinking (e.g., rumination) often involves negative thoughts that persist as individuals attempt to push them out of mind. Given the emotional nature of intrusive information that can repeatedly enter working memory, it is important to understand how the valence of information affects the ability to remove it. Participants in a non-clinical sample completed a working memory removal experiment using group-normed images with positive and negative valence. Participants encoded two images of the same valence on each trial, were cued to suppress or maintain one of them during a brief delay period, and then responded to a memory probe in which they indicated whether the test image had been presented on the current trial, regardless of whether or how it was cued. Our results demonstrate that participants were faster, relative to uncued items, to endorse an item that had been cued for maintenance, and slower to endorse an item that had been cued for suppression. Importantly, this pattern held for both positive and negative items and did not differ between valences. These findings replicate those obtained using emotionally neutral stimuli. Thus, this study demonstrates that maintenance suppression reduces the accessibility of visual information in working memory, regardless of its emotional valence, and suggests that this cognitive strategy could potentially be an effective tool in reducing intrusive thoughts that occupy the focus of attention.